PENGUATAN PERILAKU SUSTAINABILITY MELALUI KESEHATAN DAN KESELAMATANKERJA (K3) EMKM SENTRA KULINER JAMBANGAN SURABAYA - jun surjanti surjanti; Budiono Budiono; Agus Frianto; Hafid Kholidi Hadi (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2020)
The Sustainable Development Goals (SDGs) program in Indonesia must be supported by universities. Street Vendors (PKL) as part of the Micro Small and Medium Entity (EMKM) Surabaya Mining Culinary Center is mostly as a 2017 Prolink Environmental Program pilot area which is demanded to be a competitive and productive EMKM in national and global markets for sustainable development which does not yet have knowledge about sustainability and K3. Community Service Activities (PKM) provide training on sustainability and basic OSH to go to SGDs given to 30 EMKM. This activity was carried out through the collaboration of the Mandiri FE Unesa PKM Team in collaboration with the Surabaya City Cooperative and UMKM Service, Surabaya City Fire Department. This activity aims to strengthen sustanainability behavior, by: providing knowledge about how to change sustainability behavior and basic K3. Activities consist of growing sustainability behaviors and basic K3. The results of the PKM activities showed that EMKM participants in the Surabaya Mining Culinary Center were able to apply sustainability and OSH behavior to their culinary business. Furthermore, it was suggested to all relevant parties to participate in strengthening the K3 and sustainability behavior of the culinary business EMKM in Surabaya Culinary Center to accelerate the achievement of SDGs.Keywords: Behavior, Sustainability, SDGs, K3, EMKM